Administrative Use of Student Evaluation of Faculty - Haskell, Robert E. (Education Policy Analysis Archives, 1997)
In three previous papers, it was noted that while a controversial history of research on the reliability and validity of student evaluation of faculty (SEF) exists, it has not been typically viewed as an infringement on academic freedom. As a consequence, legal aspects of SEF are neither readily apparent, nor available. Moreover, SEF has not been generally seen as an infringement on, and detriment to, academic standards and quality instruction. The article is a review of SEF legal rulings analyzed in terms of their implications for academic freedom and quality of instruction in higher education.